The Impact of RSBY on Hospital Utilization and Out-of-Pocket Health Expenditure - Johnson, Douglas; Krishnaswamy, Karuna (World Bank, Washington, DC, 2015)
In 2008, India launched Rashtriya Swasthya Bima Yojana (RSBY), a government subsidized health insurance scheme for the poor that covers secondary hospital care for Below Poverty Line (BPL) households. Designed to improve access to healthcare and reduce the financial burden of healthcare expenses, RSBY currently covers 32 million households. The authors exploit the phased rollout of RSBY to estimate the impact of the scheme in its early days on hospitalization rates and out-of-pocket health expenditure using a difference-in-differences approach with matching. We use secondary data from the National Sample Survey Organization conducted in 2009-10. We find that the scheme has led to a small decrease in out-of-pocket household outpatient expenditure and consequently total medical expenditure. The authors also find limited evidence of increase in the number of households that have had a hospitalization case though there are regional variations in the nature of impact. It is unclear whether the improved access to inpatient care is reducing outpatient expenses through decreased need for outpatient care or because some people or hospitals are colluding to convert outpatient treatment to inpatient to avail of the scheme. The authors suggest that additional evidence with a more recent data set allowing for more time for RSBY to display effects is needed to strengthen these early findings.